2016
DOI: 10.1055/s-0036-1593818
|View full text |Cite
|
Sign up to set email alerts
|

Study of Various Prognostic Factors Affecting Successful Myringoplasty in a Tertiary Care Centre

Abstract: Introduction  Myringoplasty is a commonly performed otologic surgery. Objectives  The objective of this study is to evaluate the effect of prognostic factors like - size, site of perforation, status of operating ear, approach, status of contralateral ear, experience of surgeon, primary or revision myringoplasty, and smoking in graft uptake, as well as to evaluate the hearing results after myringoplasty. Methods  This is a prospective study. We included in our sample patients aged over 13 years with a Tubotym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 20 publications
1
33
1
Order By: Relevance
“…Middle ear effusion poor when the contralateral ear had tubotympanic disease (p<0.05). 21 However, in contrary to our findings and the studies mentioned above, Albera et al and Chandrasekhar et al found no statistical relationship between the condition of the contralateral ear and the final surgical outcome. 22,23 There is broad consensus about the importance of tubal function in the outcome of tympanoplasty.…”
Section: Normal Tm Perforation Tm Retractioncontrasting
confidence: 99%
“…Middle ear effusion poor when the contralateral ear had tubotympanic disease (p<0.05). 21 However, in contrary to our findings and the studies mentioned above, Albera et al and Chandrasekhar et al found no statistical relationship between the condition of the contralateral ear and the final surgical outcome. 22,23 There is broad consensus about the importance of tubal function in the outcome of tympanoplasty.…”
Section: Normal Tm Perforation Tm Retractioncontrasting
confidence: 99%
“…Regarding parameters influencing surgical outcomes, our results are in keeping with previous studies depicting the majority of variables do not cause a significant effect on outcomes [4, 7, 16, 17]. A large retrospective study of 341 pediatric cases found no difference in TMP rates by patient sex, indication for tube removal, required number of set of tubes or duration of tube retention [4].…”
Section: Discussionsupporting
confidence: 90%
“…All patients had a postoperative air-bone gap of less than 20 dB at 3 months of follow-up (Table 7). 3,5,7 In our study, the youngest patient was of 20 years and oldest patient was of 60 years. Mean age was 32.36±11.02 years.…”
Section: Resultsmentioning
confidence: 55%
“…In Kripa et al study, permeatal approach was used more commonly. 5 In our study, the most common technique used for grafting was underlay (61%), followed by overlay (24%), and interlay (15%). In a study by Sergi et al, overlay technique of grafting was most commonly used and results showed a better hearing gain in the underlay group.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation